ISIS and the Allure of Traditional Gender Roles - Speckhard, Anne (Women & criminal justice, 2023)
As issues of repatriations of ISIS members and their families are hotly debated, exploring the factors that led over 40,000 men and women to leave their home countries to join ISIS is integral to rehabilitating and reintegrating these individuals. Understanding their experiences in ISIS is critical to deradicalization. This article uses primary data to explore vulnerabilities, motivations, influences, experiences, and sources of disillusionment among ISIS members through a gender-based perspective. Men and women’s ISIS trajectories were impacted and informed by gender, particularly by a desire to solidify masculine and feminine identities in ISIS’s Caliphate, where traditional gender roles were both glorified and brutally enforced.